Research of the Influence of Bearing Clearance on the Transmission Efficiency of Gearbox - Mo Yimin; Xu Wei; Hu Jie; Dong Jixing; Li Lusheng (Jixie chuandong)
For the problem that the friction power loss of the deep groove ball bearing will directly affect the transmission efficiency of the gearbox,the composition of the friction torque of deep groove ball bearing under quasi-static condition is analyzed. By changing the size of the bearing clearance to reduce the friction power loss is also proposed and a bench test to explore the influence of the bearing clearance on the transmission efficiency of the gearbox is designed. Finally,the experiments of the whole vehicle taxiing resistance and fuel consumption are verified. The result shows that properly increasing the bearing clearance can reduce the friction power loss of deep groove ball bearing and improve transmission efficiency,it also can increase the vehicle taxi distance and reduce the vehicle fuel consumption. This study provides a reference for the selection of bearing clearance of gearbox.